Simulation and experimental research on ultrasonic drawing of copper shaped wires. (September 2019) - Liu, S; Xie, T; Cao, H Q; Shan, X B
Abstract: Ultrasonic vibrations contribute to drawing force reduction and surface finish improvement in the production of round wires. However, their effects on the drawing of irregular-shaped wires are rarely reported, as the process involves not only the shrinkage but also the reshaping of the cross-sections, which increases the difficulty in both numerical and experimental research. This work aims to investigate the influences of ultrasonic amplitude, drawing velocity, and area reduction ratio on the drawing force during the manufacturing of copper wires with rectangular, pentagon, and hexagon cross sections. The surface microtopography of the wire products was inspected using the Leica digital microscope and Hitachi scanning electron microscope (SEM). A remarkable drawing force reduction by up to 47% was observed when ultrasonic vibrations were added, especially for larger ultrasonic amplitude and lower drawing velocity occasions. The surface finish, however, was actually worse compared with under conventional drawing conditions, especially when ultrasonic amplitude exceeded 7 μm. This paper provides a potentially valuable method to enhance the efficiency of industrial production of irregular-shaped wires.